Diagnostic Value of Endotracheal Tube-Aspirate Soluble Triggering Receptor Expressed on Myeloid Cells-1 Concentration for Neonatal Ventilator-Associated Pneumonia - Zhou, Jian; Zhou, Jingqian; Hong, Yan; Wang, Youcheng; Lin, Hailong; Huang, Leting (Frontiers in Pediatrics, 2021)
Background: Soluble triggering receptor expressed on myeloid cells-1 (sTREM-1) is regarded as a biological marker of infection. We aimed to evaluate the diagnostic value of endotracheal tube (ETT)-sTREM-1 concentration in neonatal ventilator-associated pneumonia (NVAP), to explore the difference of (ETT)-sTREM-1 between preterm and full-term, and to investigate the influence of extrapulmonary infection on (ETT)-sTREM-1 concentration. Methods: In this multicenter, controlled clinical trial of 60 preterm and 33 full-term neonates on mechanical ventilators, we measured concentrations of ETT-aspirate and serum sTREM-1, serum C-reactive protein, and serum procalcitonin, as well as white blood cell count. We initially divided cases into eight groups, based on three categories: preterm of full-term; NVAP or non-NVAP; and extrapulmonary infection present or absent. Groups were compared, and logistic regression analysis and receiver operating characteristic (ROC) analysis was performed to determine diagnostic value. Results: The mean gestational age (± standard deviation) of preterm and full-term neonates was 28.9±2.2 weeks and 39.5±1.7 weeks, respectively, and 32/60 were male. The ETT-aspirate sTREM-1 concentration was higher in NVAP cases than in non-NVAP cases, irrespective of extrapulmonary infection. ROC analysis revealed that ETT-aspirate sTREM-1 concentration had an area under the curve (AUC) of 0.986 and a cutoff value of 228.0 pg/ml (sensitivity, 94.3%; specificity, 96%) in preterm neonates; the same values in full-term neonates were 0.938 and 245.5 pg/ml (sensitivity, 100%; specificity, 93.7%), respectively. The optimal combination of indicators was ETT-aspirate sTREM-1 and serum C-reactive protein concentration. All indicators were present at lower levels on days 8 and 10 of ventilation in neonates who ultimately recovered than in those who did not. Conclusions: ETT-aspirate sTREM-1 and serum C-reactive protein concentrations may be useful for the diagnosis of NVAP.